Treatment of bacterial meningitis with ceftizoxime. - Overturf, G D (1984)
Ceftizoxime was evaluated in the treatment of 18 patients (6 adults and 12 children) with bacterial meningitis. In seven patients Haemophilus influenzae was the causative agent, in three Neisseria meningitidis, in five Streptococcus pneumoniae, and in one each alpha-streptococcus and Escherichia coli; one case was culture negative. Ceftizoxime was administered intravenously in doses of 200 mg/kg per day. Clinical response was appropriate in all patients with a mean time of defervescence of 3.7 days, and sterile cerebrospinal fluid was obtained from all patients at 24 to 36 h after initiation of therapy. The mean concentration of ceftizoxime in 46 cerebrospinal fluid samples obtained during therapy was 8.53 micrograms/ml (range, less than 0.5 to 29.0 micrograms/ml). Ceftizoxime concentrations in cerebrospinal fluid samples were ten- to several hundredfold the bactericidal concentrations of the pathogens isolated from the cerebrospinal fluid. Ceftizoxime penetrates the meninges well during acute infection and appears to be an excellent candidate antibiotic in the treatment of bacterial meningitis.